2019
DOI: 10.1016/j.micpath.2019.103785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transmission potential and pathobiological characteristics of mallard originated Avian orthoavulavirus 1 (sub-genotype VII.2) in commercial broilers

Abstract: Newcastle disease (ND), caused by Avian orthoavulavirus 1 (AOAV-1), affects multiple avian species around the globe. Frequent disease outbreaks are not uncommon even in vaccinates despite routine vaccination and, in this regards, viruses of diverse genotypes originating from natural reservoirs (migratory waterfowls) play an important role in a disease endemic setting. Though genomic characterization of waterfowl originated viruses has been will-elucidated previously, there is a paucity of data on clinico-patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Regarding genotype VII.1.1 (VIId), it has been shown that pigeons are an efficient source of infection with this virus for in-contact chickens. Similarly, the mallard-originated VII.2 strain was shown to be readily transmissible to and between chickens ( 51 ). Recently, Hicks and colleagues conducted a phylodynamic analysis of the complete F gene sequences of AOAV1.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding genotype VII.1.1 (VIId), it has been shown that pigeons are an efficient source of infection with this virus for in-contact chickens. Similarly, the mallard-originated VII.2 strain was shown to be readily transmissible to and between chickens ( 51 ). Recently, Hicks and colleagues conducted a phylodynamic analysis of the complete F gene sequences of AOAV1.…”
Section: Discussionmentioning
confidence: 99%